Psychosocial characteristics of adolescents with different profiles of individuation in relation to parents - Melita Puklek Levpušček (Psihološka Obzorja, 2003)
Individuation in relation to parents represents an important developmental task during adolescence. The article focuses on the examination of different profiles of individuation in relation to parents and how these profiles manifest themselves in different periods of adolescence. We were also interested in the psychosocial characteristics that vary among adolescents with different profiles of individuation. The sample consisted of 593 adolescents in the age range of 13 to 18 years. The adolescents filled in the self-report questionnaires of individuation in relation to parents and friends, perceived parental behavior, and perceived self-efficacy in learning. They also reported about the frequency of psychological symptoms experienced in the last month. To identify the diverse groups of adolescents the scores on the scale of individuation in relation to parents were subjected to a cluster analysis. Finally, the four-cluster solution was chosen. The clusters were named: Good connectedness with parents with non-threatened autonomy, Highly harmonious relationship with parents with non-threatened autonomy, Cold relationship with parents with threatened autonomy and Ambivalent relationship with parents. The results confirmed the hypothesis, that most adolescents will be classified in the profiles of good relationship with parents with non-threatened autonomy. The results also showed that the combination of moderate emotional connectedness with parents, low parental idealization, ability to integrate autonomy and connectedness, low denial of dependency needs and low engulfment anxiety represent the most favorable individuation pattern for psychological adaptation of adolescents.